2016
DOI: 10.1175/jas-d-16-0031.1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Vertical Structure of Large-Scale Vertical Motion in Tropical Climate: Moist Static Energy Framework

Abstract: Interactions between cumulus convection and its large-scale environment have been recognized as crucial to the understanding of tropical climate and its variability. In this study, the moist static energy (MSE) budget is employed to investigate the potential impact of the vertical structure of large-scale vertical motion in tropical climate based on results from both reanalysis data and model simulation. Two domains are selected over the western and eastern Pacific with vertical motion profiles that are domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 34 publications
3
29
0
Order By: Relevance
“…A recent study by Bui et al (2016) indicated that the very different results of the vertical transport of moist static energy (MSE) between the western and eastern Pacific ITCZs (e.g., positive column-integrated vertical MSE transport in the western Pacific and negative column-integrated vertical MSE transport in the eastern Pacific) should come from different shapes of vertical motion in these two regions.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent study by Bui et al (2016) indicated that the very different results of the vertical transport of moist static energy (MSE) between the western and eastern Pacific ITCZs (e.g., positive column-integrated vertical MSE transport in the western Pacific and negative column-integrated vertical MSE transport in the eastern Pacific) should come from different shapes of vertical motion in these two regions.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The motivation behind this design was to highlight the relationship between the vertical structure of convection and precipitation intensity in a climatological (or statistical) sense (Bui et al 2016). Even though there are many studies focusing on the time-mean rainfall patterns [Neelin (2007) and reference therein], investigation on changes of precipitation characteristics is needed, especially when the intensity and frequency of both heavy and light precipitation events…”
Section: The Dependence Of Convective Vertical Structure On Precipitamentioning
confidence: 99%
See 3 more Smart Citations